3360=56*60h

Simple and best practice solution for 3360=56*60h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3360=56*60h equation:


Simplifying
3360 = 56 * 60h

Multiply 56 * 60
3360 = 3360h

Solving
3360 = 3360h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-3360h' to each side of the equation.
3360 + -3360h = 3360h + -3360h

Combine like terms: 3360h + -3360h = 0
3360 + -3360h = 0

Add '-3360' to each side of the equation.
3360 + -3360 + -3360h = 0 + -3360

Combine like terms: 3360 + -3360 = 0
0 + -3360h = 0 + -3360
-3360h = 0 + -3360

Combine like terms: 0 + -3360 = -3360
-3360h = -3360

Divide each side by '-3360'.
h = 1

Simplifying
h = 1

See similar equations:

| (x^9)(y^3)-y=x | | 2x-20=4x | | 35=-5+2x-7y | | x-30=14-(3x) | | 6x-(4x+2)=10 | | x+1=-6x | | 5w-2=-32 | | 3b^3+22b^2-80b=0 | | 4-12x=-8x | | x+x+10+x+5=180 | | 0.40m-14=9+0.60m | | -6(2y-12)=-108 | | 12n^2+54n-210=0 | | 44x^2-4x+5=4x+6 | | 6y-2-7=37 | | 6a+7=3a+1 | | h(x)=x(3)-4 | | R+7r=18 | | 268=11*80 | | Z^2+6+13=0 | | 2+n=n+2 | | -4(w-5)(-w-7)=0 | | X+10+x+x+5=180 | | 12-2b+8b=b+2 | | 12-2b+=b+2 | | 7p^2-5p-2=0 | | h(-1)=3(-1)+4 | | 2x^2-16x+64=36 | | 3x-9-8x= | | y=50-3x | | lx-6l=-7 | | 3m-16+5m=m+20+4m |

Equations solver categories